Monoclonal gammopathy‐associated pure red cell aplasia. (21st March 2016) - Korde, Neha; Zhang, Yong; Loeliger, Kelsey; Poon, Andrea; Simakova, Olga; Zingone, Adriana; Costello, Rene; Childs, Richard; Noel, Pierre; Silver, Samuel; Kwok, Mary; Mo, Clifton; et al.
Summary: Pure red cell aplasia (PRCA) is a rare disorder characterized by inhibition of erythroid precursors in the bone marrow and normochromic, normocytic anaemia with reticulocytopenia. Among 51 PRCA patients, we identified 12 (24%) patients having monoclonal gammopathy, monoclonal gammopathy of undetermined significance or smouldering multiple myeloma, with presence of monoclonal protein or abnormal serum free light chains and atypical bone marrow features of clonal plasmacytosis, hypercellularity and fibrosis. Thus far, three patients treated with anti‐myeloma based therapeutics have responded with reticulocyte recovery and clinical transfusion independence, suggesting plasma cells play a key role in the pathogenesis of this specific monoclonal gammopathy‐associated PRCA.